CDH1‐related blepharocheilodontic syndrome is associated with diffuse gastric cancer risk. Issue 7 (17th April 2020) - LeBlanc, Shannon; Naveen, Dildeepa; Haan, Eric; Barnett, Christopher; Rawlings, Lesley; Roscioli, Tony; Poplawski, Nicola
Abstract: We report the first case of diffuse gastric cancer in an individual with familial blepharocheilodontic syndrome (BCD) due to a germline CDH1 likely pathogenic variant. To date, other BCD affected relatives are nonpenetrant for diffuse gastric cancer posing challenges to counseling regarding gastric and breast cancer surveillance, and preventative total gastrectomy.